Dermatological diseases of the feet in Turkey: The analysis of 634 patients (Annals of Medical Research, 2021)
Aim: Dermatological diseases of the feet may be hereditary, inflammatory, infectious or malignant. The patients may be primarily evaluated by general surgeons, orthopedists, primary care physicians and podiatrists. Moreover, foot health centers are becoming increasingly popular. Therefore, we aimed to determine the most common skin disorders affecting the feet to guide the physicians in managing of skin-related foot disorders.Material and Methods: Between March 2017 and March 2019, 634 patients (55.5% female, 44.5% male) with skin disorders affecting feet were included in this study. The patients were evaluated in three groups according to the age including younger than 18, between the age of 18-65, and older than 65.Results: The most common disease group and skin disease observed in all patients were infections 272 (42.9%) and onychomycosis 106 (16.7%), respectively. Onychomycosis was followed by ingrown nail 67 (10.6%), tinea pedis 56 (8.8%) and warts 53 (8.4%). The most common disease group and skin disease were infections 18 (34.6%) and ingrown nail 17 (32.7%) in patients younger than 18, and infections 199 (45%) and onychomycosis 76 (17.2%) in patients aged 18-65. Similarly, infections 55 (39.3%) and onychomycosis 27 (19.3%) were the most common disorders observed in patients older than 65.Conclusion: This study revealed that the most common skin diseases affecting feet were onychomycosis, ingrown nail, tinea pedis and warts. However, frequency of these disorders varied depending on age. These results will guide the physicians in making diagnosis, differential diagnosis or referring the patients to a specialist when needed.
Keywords: Foot; nails; skin diseases